Republic of Lithuania : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Lithuania. (IMF Staff Country Reports; Country Report ;, 2021)
With a demonstrated resilience to the crisis and the recovery gaining strength, macroeconomic policies should aim at preserving stability and complementing structural reforms that address long-standing challenges. A medium-term plan to rebuild buffers, support potential growth, and target pockets of vulnerability would help address pre-existing disparities and poverty. Sustained productivity growth, supported by the implementation of politically difficult but needed structural reforms, is the only way to support high wage growth and convergence with Western Europe. Failure to do so could jeopardize Lithuania's hard-earned competitiveness gains.